The Polarisation of Information through Illocutionary Speech Acts in Kakakitwill’s Tiktok Social Media Account - Brinda, Sonya; Ardiyanto, Fahrur Rijal; Swandana , Irwan (Journal of ELT, Linguistics, and Literature, 2025)
Post-truth phenomenon has already been a common issue in this digital era. On the other hand, as the effect of this digital era growth, society who could be addressed as digital society, can access the digital products like smartphone or computer to gain information easily from social media. Thus, social media took the important role by spreading the information and making a mass. In this matter, influencers on social media had the big opportunity in leading the opinion to the desired side. Influencers had their power through their words to the followers which can be analysed from the speech acts on their social media accounts. Then, this study focused on the illocutionary speech acts from a TikTok influencer who can be addressed as one of the LGBTQIA+ community, and how the gesture and speech can affect the polarisation of information to the digital society by using the descriptive qualitative method. Illocutionary speech acts is one of the pragmatics focuses, which analyse the meaning of speech based on the context. Furthermore, LGBTQIA+ issue was not a new thing, because this issue has been spreading and growing wild these days. Norms were overthrown by this social phenomenon as the result in polarisation of information which being led by the LGBTQIA+ influencers.